2021
DOI: 10.33650/ijoeel.v3i1.2062
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Interference in English Communication Used by Nurul Jadid Students

Abstract: Interference is one of the factors that can undermine a language system. Generally, interference often occurs in the language learning process. The interference is caused by a tendency to accustom the pronunciation of one language to another. Its scope includes changes in sound form, grammar, sentence structure, and vocabulary. Nurul Jadid Islamic boarding school is one of the boarding schools that develops foreign language skills as an attempt to prepare young people to be able to compete in the global world.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The language interference happens in all language components, such as phonology, morphology and syntax. Weinrich (1953) in (Hikmah et al, 2021) stated Interference which happens in morphology and syntax can be called as grammatical interference. In accordance, (Ekawati, 2018) also concluded that the influence of language 1 pattern to targeted language structure because of its similarity and difference is called grammatical interference.…”
Section: Introductionmentioning
confidence: 99%
“…The language interference happens in all language components, such as phonology, morphology and syntax. Weinrich (1953) in (Hikmah et al, 2021) stated Interference which happens in morphology and syntax can be called as grammatical interference. In accordance, (Ekawati, 2018) also concluded that the influence of language 1 pattern to targeted language structure because of its similarity and difference is called grammatical interference.…”
Section: Introductionmentioning
confidence: 99%